Antibodies directed against endogenous and exogenous citrullinated antigens pre-date the onset of rheumatoid arthritis - Johansson, Linda; Brink, Mikael; Ärlestig, Lisbeth; Bartaloni, Debora; Rantapää Dahlqvist, Solbritt; PRATESI, FEDERICO; D'AMATO, CLAUDIA; MIGLIORINI, PAOLA (Arthritis Research & Therapy, 2016)
Background: Anti-citrullinated-peptide antibodies (ACPA) have been detected in individuals with developing rheumatoid arthritis (RA) before the onset of symptom, with an initially limited spectrum of reactivities that gradually broadens. The aim was to analyze the evolution of ACPA response pre-dating symptom onset, using four selected citrullinated exogenous and endogenous antigens. Methods: A cohort of 521 individuals sampled before symptoms of RA appeared and 272 population controls were identified from the Biobank of Northern Sweden; 241 samples from patients with early RA were also collected. ACPA were detected by ELISA on viral citrullinated peptides (VCP) derived from Epstein-Barr-virus nuclear antigen (EBNA)1 and EBNA2 (VCP1 and VCP2) and histone-4-derived citrullinated peptides (HCP1 and HCP2). Results: In pre-symptomatic individuals vs. patients with early RA, anti-VCP1 antibodies were detected in 10.4 % vs. 36.1 %, anti-VCP2 in 17.1 % vs. 52.3 %, anti-HCP1 in 10.2 % vs. 37.3 %, and anti-HCP2 in 16.3 % vs. 48.5 %, respectively. Anti-VCP and anti-HCP concentrations were significantly increased in pre-symptomatic individuals vs. controls (p < 0.001) and were increased approaching symptom onset. Anti-VCP and anti-HCP appeared simultaneously (median (IQR) 5.3 (6) years before symptom onset) and in combination yielded a high-risk ratio for disease development (OR = 8.0-18.9). Anti-VCP2 and anti-HCP2 antibodies were associated with HLA-DRB1*0401 in pre-symptomatic individuals. Three peptidylarginine deiminase (PAD)I3/PADI4 single nucleotide polymorphisms (SNPs) were significantly associated with anti-HCP1. Conclusions: Anti-VCP and anti-HCP antibodies pre-date symptom onset and predict disease development, but no hierarchy of citrullinated epitopes can be identified. These results suggest that no inciting citrullinated antigen so far described is common to all patients with RA. The association between PADI3/PADI4 polymorphism and anti-HCP1 antibodies suggests a novel link between deimination and ...